Evaluation of An Ecological Program to Reduce Bullying in Schools - Rahey, Leila; Craig, Wendy (Canadian Journal of Counselling and Psychotherapy, 2007)
Recently researchers have made efforts to reduce the incidence of bullying in the schools using a systemic or Whole School Approach. Reports on the efficacy of antibullying programs have produced variable, but promising, results ( Elsea & Smith, 1998; Olweus, 1993; Pepler, Craig, Charach, & Ziegler, 1993). The present study examined the short-term outcome of an antibullying program by comparing children (grades 1-8) attending a school involved in the program to children attending a school not receiving the program. Results indicated that bullying did not decrease four months after the antibullying program was introduced. There were, however, improvements reported in the level of victimization, peer isolation, and perceptions of school safety in older children (grades 3-8). Contradictory findings were found for younger children (grades 1 and 2). Implications and limitations of the study are discussed from a systemic perspective.